An intelligent adaptive participant's presumption protocol for atomic commitment in distributed databases. (1st January 2013) - Al-Houmaily, Yousef J.
The objective of the original 'adaptive participant's presumption protocol' (AP 3 ) was to achieve the performance advantages of one-phase commit protocols, whenever possible, and, at the same time, the wide applicability of two-phase commit protocols. Specifically, AP 3 operates as a one-phase commit protocol for the commit processing of a transaction so long as the transaction is not associated with the validation of any deferred consistency constraints. But, when a transaction is associated with the validation of deferred consistency constraints that need to be synchronised at commit time of the transaction, AP 3 dynamically switches to the most appropriate two-phase commit variant. However, providing further intelligence to enhance the performance and applicability of the original AP 3 is expected to make it a highly appealing choice for adoption in the design of future distributed database management systems. This is the essence of the 'intelligent AP 3 ' that extends the basic AP 3 in two directions: efficiency and applicability .